Limits of Growth Modulation Using Tension Band Plates in the Lower Extremities. Issue 10 (October 2016) - Shabtai, Lior; Herzenberg, John E.
Abstract : Growth modulation using tension band plates (TBP) has been shown to be a safe, effective, and popular method for correcting pediatric frontal plane angular deformity around the knee. Recently, TBPs have been used to achieve reversible epiphysiodesis to treat limb-length discrepancy. Many surgeons have expanded the indications to include diagnoses other than frontal plane angular deformities, anatomic sites other than the knee, and correction of sagittal and oblique plane deformities. Despite the rapid acceptance of TBPs, the limits of this option have not been explored. We undertook a systematic literature review and found that the success rate for idiopathic cases approaches 100% with a low complication rate. Pathologic cases have a slightly lower success rate and a higher complication rate. The potential to avoid osteotomy with growth modulation makes TBPs a reasonable option for all but the most extreme pediatric frontal and sagittal plane lower extremity deformities. Applications to hip deformities remain unproven.